Ox-LDL Causes Endothelial Cell Injury Through ASK1/NLRP3-Mediated Inflammasome Activation via Endoplasmic Reticulum Stress - Hang L; Peng Y; Xiang R; Li X; Li Z (Drug Design, Development and Therapy, 2020)
Liwei Hang, 1–5,* Yan Peng, 6,* Rui Xiang, 7 Xiangdong Li, 8 Zhiliang Li 1–4 1Department of Cardiology, Heart Center, Zhujiang Hospital, Southern Medical University, Guangzhou, Guangdong 510280, People’s Republic of China; 2Laboratory of Heart Center and Department of Cardiology, Heart Center, Zhujiang Hospital, Southern Medical University, Guangzhou, Guangdong 510280, People’s Republic of China; 3Guangdong Provincial Biomedical Engineering Technology Research Center for Cardiovascular Disease, Guangdong, Guangdong 510280, People’s Republic of China; 4Sino-Japanese Cooperation Platform for Translational Research in Heart Failure, Guangzhou, Guangdong 510280, People’s Republic of China; 5Department of Cardiology, Dongsheng People’s Hospital, Erdos City, Inner Mongolia 017000, People’s Republic of China; 6Department of Critical Care Medicine, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 7Department of Cardiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 8Fuwai Hospital, National Center of Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100037, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiliang LiDepartment of Cardiology, Heart Center, Zhujiang Hospital, Southern Medical University, No. 253 Industrial Avenue, Haizhu District, Guangzhou, Guangdong 510280, People’s Republic of ChinaTel +86-020-62782250Email lizhiliang020@126.comXiangdong LiFuwai Hospital, National Center of Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 167 Beilishi Road, Beijing 100037, People’s Republic of ChinaTel +86-010-88392557Email fuwai_lxd@163.comObjective: This study was to investigate the mechanism of inflammatory pathology modification induced by ox-LDL in endothelial cells.Methodology: In this study, we firstly investigated the efflux of cholesterol of endothelial cells under the treatment of ox-LDL, and cell proliferation, ROS production, cell apoptosis was measured. Further, proteins of ASK1, NLRP3 inflammasomes and endoplasmic reticulum stress response were detected. Afterwards, ASK1 inhibitor (GS-4997) or endoplasmic reticulum stress (ERS) inhibitor (4-PBA) was used to measure the performance of endothelial cells.Results: In this study, endothelial cells were treated with ox-LDLs alone or in combination with a GS-4997 or 4-PBA. Results showed that ox-LDLs attenuated the efflux of cholesterol from endothelial cells in a dose-dependent manner. Ox-LDLs inhibited the proliferation of endothelial cells, and induced their apoptosis and production of reactive oxygen species (ROS). Additionally, ox-LDLs upregulated the levels of phosphorylated ASK1, ERS-related proteins (chop, p-PERK, GRP78, and p-IRE-1), and inflammation-associated proteins (NLRP3, IL-1β, and caspase 1) in endothelial cells. Moreover, we proved that GS-4997 could partly reverse ox-LDL-mediated cell proliferation, apoptosis, ROS production, and inflammation in endothelial cells, and increase cholesterol efflux. We also found that 4-PBA could attenuate the effects of ox-LDLs on endothelial cell cholesterol efflux, proliferation, apoptosis, ROS production, and inflammation.Conclusion: Our results suggest that cholesterol efflux from endothelial cells is reduced by ox-LDLs, and these reductions in cholesterol efflux are accompanied by increased NLRP3 inflammasome signaling, ASK1 and higher levels of endoplasmic reticulum stress. Our results suggest this axis as potential targets for treating atherosclerosis.Keywords: ox-LDL, endoplasmic reticulum stress, cholesterol efflux, inflammatory corpuscles, endothelial cell, apoptosis signal-regulating kinase 1